2020
DOI: 10.1371/journal.pone.0226392
|View full text |Cite
|
Sign up to set email alerts
|

Research performance and age explain less than half of the gender pay gap in New Zealand universities

Abstract: We use a globally unique dataset that scores every individual academic's holistic research performance in New Zealand to test several common explanations for the gender pay gap in universities. We find a man's odds of being ranked professor or associate professor are more than double a woman's with similar recent research score, age, field, and university. We observe a lifetime gender pay gap of~NZ$400,000, of which research score and age explain less than half. Our ability to examine the full spectrum of rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
87
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(103 citation statements)
references
References 70 publications
(65 reference statements)
2
87
0
1
Order By: Relevance
“…Drawing on a comprehensive New Zealand data set, Brower and James (2020) found that a male academic's odds of achieving a professorial or associate professorial position were more than double a woman's odds with a similar research score, age, field and university-and the odds were higher still if attention was only focused on achieving a full professorial position.…”
Section: The Gendered Character Of Academiamentioning
confidence: 99%
“…Drawing on a comprehensive New Zealand data set, Brower and James (2020) found that a male academic's odds of achieving a professorial or associate professorial position were more than double a woman's odds with a similar research score, age, field and university-and the odds were higher still if attention was only focused on achieving a full professorial position.…”
Section: The Gendered Character Of Academiamentioning
confidence: 99%
“…Organisers frequently report that they tried to get female representation but failed, or else that there are no women at a suitable level within the discipline. Disproportionate representation of women is also seen in applicants for academic jobs, where the proportion of female applicants is commonly < 30 % and sometimes < 10 % (Ceci et al, 2014). Chairs of selection committees are sometimes asked to improve diversity of their applicant lists, to which they often reply that they have exhausted their networks and known potential applicants but the women are just not there.…”
Section: The Role Of Women-focused Geoscience Networkmentioning
confidence: 99%
“…At the start of 2020, Bristol became the first university in Britain to commit to tackling its gender pay gap, which at 13.6% was actually lower than the national average in higher educational institutes of 15.1% ( http://bristol.ac.uk/ news/2020/january/gender-pay-gap-agreement.html ). A study published the same month reported that women academics in New Zealand would earn as much as $40 0,0 0 0 less over their career than their male colleagues [20] . In the US, sizeable pay discrepancies were reported in a study of the major federal health and science agencies; whilst the largest of these was in the National Science Foundation (ratio women: men 0.73), the National Institutes for Health (NIH) responded: 'The NIH takes the gender wage gap issue seriously and knows that there is additional work to be done' ( https://www.nature.com/articles/d41586-020 -0 0 023 -6 ).…”
Section: Universities/ Hospitalsmentioning
confidence: 99%